IMPLEMENTASI PEMBELAJARAN HANDS ON ACTIVITIES UNTUK MENINGKATKAN SIKAP TERHADAP SAINS PADA SISWA SMP - Said, Mohamad; ', Azizahwati; ', Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research aims to determine the increase attitudes toward science of students in physic learning by the implementation of hands on activities in class VIII SMPN 20 Pekanbaru. The subjects are students of class VIII3. This class has fewer than 39 students. The data collection instrument in this study is questionnaire of attitudes towards science which consists of 37 statements. Analysis of the data in this study is a descriptive analysis using the gain (increase). If G > 0.3, so the attitude towards science of student is increase by the implementation of hands on activities. The results of all indicators showed: Gain student’s attitudes toward science for indicator fun science is 0.09 with a low category, classroom or teacher is 0.08 with a lower category, self directed efforts is 0.14 with a low category, anxiety toward science is 0.16 with a lower category, family model is 0.15 with a low category. So that the average gain attitudes toward science of students in the amount is 0.12 to a low category. Application of hands on activities of material pressure have a low gain to improve attitude science of students in class VIII3 SMPN 20 Pekanbaru.Key Words: attitudes towards science, hands on activities learning